Experimental study of a slit in the presence of a bias flow under medium- and high-level acoustic excitations. Issue 2 (June 2023) - Aulitto, Alessia; Hirschberg, Avraham; Lopez Arteaga, Ines; Saxena, Vertika
This work presents an experimental investigation of the acoustic properties of a slit in the presence of a bias flow under moderate- and high-acoustic excitations. Impedance tube experiments are discussed for a geometry inspired by deep punching resulting in a cut in the plate. The acoustic transfer impedance of the plate is discussed for several bias flow velocities, acoustic excitation, and different frequencies. In the range considered for this study, a bias flow appears to have two main effects, globally enhancing the sound absorption of the plate and creating a protective layer downstream of the plate due to the interaction between the slits. A maximum of the enhancement factor is found at a specific ratio between the acoustic velocity and the bias flow velocity. Two simple asymptotic behaviors are found, dominated by the flow or by the acoustic excitation, respectively. The behavior of the inertance is complex. Globally the inertance decreases with decreasing flow Strouhal number while its dependency on the amplitude of the acoustic velocity is less obvious.